Faktor Determinan Taksiran Berat Janin Ibu Hamil Di Palangkaraya - Christine Aden (Jurnal Forum Kesehatan, 2018)
During pregnancy, fetal growth and development is expected to increase in order to avoid low birth weight or less than 2500 grams. Many factors play a role in fetal growth in late pregnancy. This study aimed to identify factors in pregnant women which are to know the relation and the influence of factors with estimated fetal weight in the third trimester pregnant women in Palangka Raya. The data were analyzed by Pearson Correlation test, unpaired T test, ANOVA test and linear regression test. There was no correlation between the estimated fetal weight with maternal age (p>0,05), with a range of pregnancy (p>0,058), with ante natal care (p=0,05), with family (p=0,146), There was a correlation between the estimated fetal weight with gestational age (p=0,000), with parity (p=0,018), with the mother's nutrition (p=0,000), education (p=0,001), the knowledge of the mother (p=0,021). Gestational age, maternal nutritional status, and education level are able to explain 39,3 % estimated fetal weight and the rest 60,7%, be explained by other factors. This research is expected to provide benefits for service improvement and education also the development of science and the decision maker to increase estimated fetal weight in pregnant women